Pattern of Cutaneous Allergy in the Dermatology Department of TUTH (2005-2007) - Pokhrel, Dinesh Binod; Joshi, D. D.; Bohara, M. S. (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Allergy; Disorder; Urticaria; Polymorphic light eruption DOI: 10.3126/jnhrc.v5i2.2469 Journal of Nepal Health Research Council (JNHRC) Vol. 5, No.2, October 2007 33-38